2012
DOI: 10.1038/leu.2012.298
|View full text |Cite
|
Sign up to set email alerts
|

The transporter ABCB7 is a mediator of the phenotype of acquired refractory anemia with ring sideroblasts

Abstract: Refractory anemia with ring sideroblasts (RARS) is characterized by mitochondrial ferritin (FTMT) accumulation and markedly suppressed expression of the iron transporter ABCB7. To test the hypothesis that ABCB7 is a key mediator of ineffective erythropoiesis of RARS, we modulated its expression in hematopoietic cells. ABCB7 up and downregulation did not influence growth and survival of K562 cells. In normal bone marrow, ABCB7 downregulation reduced erythroid differentiation, growth and colony formation, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 34 publications
8
80
0
2
Order By: Relevance
“…Before examining this issue, we want to 23,24 whereas a recent study has shown altered ABCB7 exon usage in primary RARS cells. 36 The interconnection between DNA transcription and RNA splicing, illustrated in Figure 2, is consistent with the conclusion that a somatic SF3B1 mutation may result in reduced transcription and abnormal splicing of ABCB7. SF3B1 mutations showed a non significant trend toward longer survival.…”
Section: Prognostic Relevance Of Sf3b1 Mutations In Mdssupporting
confidence: 65%
See 1 more Smart Citation
“…Before examining this issue, we want to 23,24 whereas a recent study has shown altered ABCB7 exon usage in primary RARS cells. 36 The interconnection between DNA transcription and RNA splicing, illustrated in Figure 2, is consistent with the conclusion that a somatic SF3B1 mutation may result in reduced transcription and abnormal splicing of ABCB7. SF3B1 mutations showed a non significant trend toward longer survival.…”
Section: Prognostic Relevance Of Sf3b1 Mutations In Mdssupporting
confidence: 65%
“…A recent study by Nikpour et al has tested the hypothesis that a reduced expression of ABCB7 plays a role in the pathophysiology of RARS. 36 The investigators showed that down-regulation of ABCB7 led to markedly reduced erythroid growth in vitro with accumulation of mitochondrial ferritin in immature RBCs. In addition, normalization of ABCB7 expression in RARS erythroblasts rescued aspects of the RARS phenotype.…”
Section: Relationship Between Sf3b1 Mutations and Ring Sideroblasts Imentioning
confidence: 99%
“…12,26,[28][29][30] Other studies suggested the relationship between SF3B1 mutations and mitochondrial proteins but did not delve into the specific mechanisms or pathways that contribute to iron accumulation or disease phenotype in SF3B1-mutant MDS. 10,31 Using TEM, we found that within RARS/-T, sideroblasts of SF3B1-mutant patients have distinct ultrastructural iron distribution characterized by abundant iron deposits compared with those of WT patients. 12 In the present manuscript, we confirmed that TEM is able to detect a difference in the iron content between mutant and WT RARS/-T patients not appreciated by conventional Prussian blue staining.…”
Section: Discussionmentioning
confidence: 97%
“…A distinguishing feature of the disease is the presence of iron- loaded mitochondria (sideroblasts), and defects in heme metabolism with protoporphyrin IX accumulation [273275]. Defects in ABCB7 have also been proposed to mediate ineffective erythropoiesis in refractory anemia with ring sideroblasts (RARS) [276, 277], a myelodysplastic syndrome (MDS) characterized by mitochondrial ferritin (FTMT) accumulation, and in the refractory anemia with ring sideroblasts and isodicentric (X)(q13) chromosome [278]. It seems that the anemia and the ataxia observed in XLSA/A are related to altered iron homeostasis which leads to mitochondrial iron accumulation in developing red blood cells and in neural cells [279, 280].…”
Section: X-linked Sideroblastic Anemia With Cerebellar Ataxia (Xlsa/amentioning
confidence: 99%